Vigour Test to Predict Seed Germination and Normal Seedling Emergence of Acacia mangium in Nursery - Endang Pujiastuti; Dede J. Sudrajat (Jurnal Perbenihan Tanaman Hutan, 2017)
Standard germination does not always indicate seed lot potential performance, especially if field germination conditions are less than optimal. Seed vigour tests therefore have been proposed to detect more accurate differences in potential seed lot performance. This study is aimed to obtain more precise method to assess Acacia mangium seed vigour correlated to germination success in a greenhouse and normal seedling emergency in a nursery. Tests were conducted on 13 seed lots collected from some certified seed sources. Seed testing and nursery activities were carried out at the Seed Laboratory of Forest Tree Seed Technology Research & Development Centre, Bogor. Experimental designs were arranged in a completely randomized design with four replications for laboratory tests (standard germination, germination index, number of normal seedling in the first count, radicle length, tetrazolium test, controlled deterioration test, accelerated aging, conductivity test), germination in a greenhouse and direct sowing in a nursery. Results showed that all tests were significantly different for ranking seed vigor in the different seed lots. Seed lot from Subanjeriji-2 provided the best germination performance in the greenhouse and direct sowingin the nursery, followed by seed lot from Parungpanjang, while seed lot from Kenangan had the lowest germination performance. The relationship between some laboratory tests, i.e. top paper test, germination index, and electrical conductivity test, and the greenhouse and nursery tests were significant. The electrical conductivity test had the highest accuracy with R2= 0,6278 for greenhouse test and R2= 0,4057 for nursery test. Overall, among all the laboratory tests, electrical conductivity test showed seeds well, so the usage of the electrical conductivity test for predicting normal seedling emergence could be suitable in A. mangium nursery programs.